PENERAPAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS EDUCANDY DALAM MENINGKATKAN MOTIVASI BELAJAR PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM - Ismail, Muh; Bunyamin, Andi; Mustamin; Wahab, Abdul; Azhar, Muh (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the implementation of Educandy-based interactive learning media in enhancing student learning motivation in the Islamic Religious Education subject for Class X A of the Computer and Network Engineering (TKJ) program at SMK Negeri 1 Topoyo, Central Mamuju Regency. The study employs the Classroom Action Research (CAR) method using both qualitative and quantitative approaches. It was conducted over two cycles, each comprising the stages of planning, action implementation, observation, and reflection. The research subjects consisted of 30 students from Class X A of the TKJ program. Data collection techniques included observation, tests, interviews, and documentation. Data were analyzed using descriptive qualitative and quantitative methods by calculating activity percentages, averages, and student learning mastery. The results indicate that the implementation of Educandy-based interactive learning media can enhance student motivation and engagement in the learning process. In Cycle I, student engagement was relatively low, characterized by a lack of attention and limited active participation in asking questions, discussions, and answering inquiries. Following improvements made in Cycle II, there was an increase in student activity and participation. An improvement was also observed in learning outcomes: the number of students achieving mastery rose from 10 (33.33%) at the initial stage to 26 (86.67%) in Cycle II, while the number of students who did not achieve mastery decreased to 4 (13.33%). Thus, the implementation of Educandy-based interactive learning media can boost learning motivation and support improved learning outcomes for students in the Islamic Religious Education subject.